Development Of Control Circuit For Single Phase Inverter Using Atmel Microcontroller. - Ismail, Baharuddin; Taib, S; Mohd Saad, A R; Isa, M; Daut, I (2006)
This paper presents the development of control circuit for single phase inverter using Atmel microcontroller. The attractiveness of this configuration is the elimination of a microcontroller to generate sinusoidal pulse width modulation (SPWM) pulses.